Supply Chain Optimization of Agricultural Products in The Internet Environment with Blockchain (Informatica, 2021)
This paper briefly introduced blockchain and agricultural product supply chain and optimized the agricultural product supply chain with blockchain. Then, an instance analysis was carried out by taking a flour mill in Sichuan Province as an example. The results showed that the supply chain-based agricultural product supply chain could be properly applied to the supply chain management of the flour mill; the supply chain that adopted blockchain technology could effectively resist abnormal data modification and ensure the reliability of supply chain information, and it could also quickly trace the faulty link in the supply chain and improve the efficiency of supply chain management.